Emergency Medical Services Response to Patients with Cardiac Arrest: A Comprehensive Review - Haitham Hamdan Khalaf Al-Alati, Ali Obaid Sayyaf Al-Daqqi, Muhammad Abdulrahman Duaibel Al-Anzi, Moageb Faleh Al-Shammari, Rawafed Al-Tayeb Al-Faki, Sami Saad Al-Harbi, Mishari Obaid Shujaa Al-Omari, Omair Sarihan Mansour Al-Bishi (Journal of International Crisis and Risk Communication Research, 2024)
Cardiac arrest remains a leading cause of mortality worldwide, requiring immediate and effective interventions to improve survival outcomes. Emergency Medical Services (EMS) play a critical role in the chain of survival, offering prompt response, advanced life support, and efficient transport to definitive care. This review examines the multifaceted approach of EMS in managing cardiac arrest, addressing the integration of basic and advanced life support measures, the significance of dispatcher-assisted CPR, and the impact of post-resuscitation care. Furthermore, it explores the challenges faced by EMS providers, including logistical, resource, and training barriers, while highlighting advancements in technology and protocols that enhance response efficacy. Emphasizing a systems-based approach, this article underscores the importance of continuous quality improvement, community involvement, and interdisciplinary collaboration to optimize outcomes for cardiac arrest patients.